Psychometric Analysis of Senior Secondary School Certificate Examination (SSCE) 2017 Neco English Language Multiple Choice Test Items in Kwara State Using Item Response Theory - Jimoh, Kasali; Aina Opesemowo, Oluwaseyi; Akintomide Faremi, Yinusa (Journal of Applied Research and Multidisciplinary Studies, 2022)
The study determined the dimensionality of 2017 National Examinations Council (NECO) English Language multiple-choice test item and estimated the item parameter indices (discrimination, difficulty, guessing and carelessness) using four parameter logistic model. The ex-post facto design was employed for the study. The population for the study comprised all candidates/test-takers who enrolled and sat for June/July Senior School Certificate Examination (SSCE) 2017 NECO English Language Examination in Kwara State, Nigeria with 12,000 samples purposively selected from sixteen Local Government Area in the State. The research instruments used for the study were Optical Marks Record Sheets for the NECO June/July 2017 English Language objectives items. The responses of the testees were scored dichotomously. The data collected were calibrated using four parameters logistic model. The results showed that the 2017 English Language multiple-choice item among SSCE students in Kwara State does not violate the assumption of unidimensionality which made the items reliable for use in assessing knowledge of students in English language. Also, the results showed that only two items were able to suit the 4-PLM based on the rule of thumb. While the remaining items does not suit the 4-PLM. It was recommended among others that NECO and other examination bodies should intensify more efforts toward improving the standard of the English Language test items using 4-PLM, which is the new trend for estimating item parameter indices